Influence of Molecular Design on the Targeting Properties of ABD-Fused Mono- and Bi-Valent Anti-HER3 Affibody Therapeutic Constructs - Mohamed Altai; Charles Dahlsson Leitao; Sara S. Rinne; Anzhelika Vorobyeva; Christina Atterby; Stefan Ståhl; Vladimir Tolmachev; John Löfblom; Anna Orlova (Cells, 2018)
Overexpression of human epidermal growth factor receptor type 3 (HER3) is associated with tumour cell resistance to HER-targeted therapies. Monoclonal antibodies (mAbs) targeting HER3 are currently being investigated for treatment of various types of cancers. Cumulative evidence suggests that affibody molecules may be appropriate alternatives to mAbs. We previously reported a fusion construct (3A3) containing two HER3-targeting affibody molecules flanking an engineered albumin-binding domain (ABD035) included for the extension of half-life in circulation. The 3A3 fusion protein (19.7 kDa) was shown to delay tumour growth in mice bearing HER3-expressing xenografts and was equipotent to the mAb seribantumab. Here, we have designed and explored a series of novel formats of anti-HER3 affibody molecules fused to the ABD in different orientations. All constructs inhibited heregulin-induced phosphorylation in HER3-expressing BxPC-3 and DU-145 cell lines. Biodistribution studies demonstrated extended the half-life of all ABD-fused constructs, although at different levels. The capacity of our ABD-fused proteins to accumulate in HER3-expressing tumours was demonstrated in nude mice bearing BxPC-3 xenografts. Formats where the ABD was located on the C-terminus of affibody binding domains (3A, 33A, and 3A3) provided the best tumour targeting properties in vivo. Further development of these promising candidates for treatment of HER3-overexpressing tumours is therefore justified.